The Effect of the Combination of Basil Leaf (Cimum Basilicum) and Bay Leaf (Syzygium Polyanthum) Boiled Water on the Level of Clansia Uric Acid in Rumpa Village - Natalia, Gabriella Delfie; Ina, Theresia (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Gout is the result of protein metabolism from foods that contain purines such as several types of food sourced from animals and have a high content of purines including, jeroun (liver, spleen, tripe), livestock (beef, horse meat and goat meat), processed (comet, sardines, cheese) increase uric acid levels, if there is an increase in uric acid levels and are marked by sciatica in the joints, Aches, pains, redness and swelling are known as gout. The prevalence of gout in Indonesia occurs under the age of 34 years by 32% and over 34 years by 68%. People with gout if not treated quickly will worsen. The objective was to determine the effect of the combination of boiled water of basil leaves (Cimum basilicum) and bay leaves (Syzygium polysnthum) on the uric acid levels of the elderly in Rumpa Village. The method used was the quasi-experimental time approach method (pretest-post test), a sample of 10 people. Results The researcher obtained a statistical test using the Paired Sample t test because after the normality test of the data obtained was normally distributed with the pre-test, a value of p0.880 (p0.05) was obtained. For the post test, a value of p0.614 (p0.05) was obtained, so it can be concluded that the data is normally distributed. This means that there is an effect of giving a combination of basil leaf boiled water (Ocimum Basilicum) and bay leaf boiled water (Syzygium Polyanthum) on uric acid levels in the elderly